Display song of parti-coloured bat Vespertilio murinus Linnaeus, 1758 (Chiroptera, Mammalia) in southern Slovenia and preliminary study of its variability - Zagmajster, Maja (Natura Sloveniae, 2003)
In September 2000, display song of parti-coloured bat Vespertilio murinus Linnaeus, 1758, was recorded for the first time in Slovenia. Bats emitted the song at four localities near Goteniška gora Mountain in southern Slovenia while flying above the canopy or above open land surrounded by forests. In thearea of Medvedjak, the display song consisted of 8 frequency modulated sweeps on average and a final frequency modulated - quasi-constant frequency call (average frequency of maximum energy in quasi-constant frequency part of the final call was 14.69 kHz). Final calls of the display song from three localities were significantly different in four measured parameters. Possible causes for this are discussed.
Keywords: Animal Communication; Behavior, Animal; Chiroptera; Echolocation; Eholokacija; Netopirji; prevalence; razširjenost; Slovenia; Slovenija; Vedenje živali; Žival, komunikacija